(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Samples of Myzus persicae strains were collected in different parts of Northern Italy during 1988 and 1989: biological tests to asses the susceptibility of these aphids to pirimicarb, ethiofencarb and heptenophos were carried out. From the LD50 values calculated, it appears that different aphid strains exibhit different levels of sensitivity to the insecticides used in the tests. Some strains, which have shown a reduced susceptibility towards an active ingredient, behave in a similar way towards others. M. persicae populations are evolving toward a resistant condition and it involves several active ingredients.